Survey study on sentinel lymph node biopsy: indications and perceived value among small animal surgical specialists - Lavinia Elena Chiti; Ester Luconi; Alessandra Ubiali; Patrizia Boracchi; Damiano Stefanello; Mirja Christine Nolff (Frontiers in Veterinary Science)
IntroductionDespite the growing adoption of sentinel lymph node biopsy (SLNB) for nodal staging in dogs, standardized guidelines defining its specific indications remain lacking. This survey study aimed to assess the indications for SLNB among small animal surgical specialists and evaluate its perceived value.MethodsAn online survey was distributed through the European College of Veterinary Surgeons (ECVS), comprising five sections: clinical practice type, nodal staging, lymphadenectomy, mapping techniques, and the perceived value of SLNB. Descriptive statistics summarized responses, while cluster analysis explored associations between clinical practice type and SLNB recommendations.ResultsSeventy-four surgeons participated, with 74% practicing in non-academic and 26% in academic institutions. The majority (80%) performed lymphadenectomy with histopathological evaluation for nodal staging, and 53% recommended it for all malignant tumors, irrespective of nodal size. Additionally, 80% preferred SLNB over regional lymphadenectomy, particularly for specific tumor types (mast cell tumors, melanomas, carcinomas) or anatomical locations (oral tumors). Indirect CT lymphography was the most commonly used preoperative mapping technique (59.4%), yet only 23% of respondents combined preoperative and intraoperative mapping techniques. While 63% considered SLNB a reliable diagnostic tool, cluster analysis indicated that the type of clinical practice (academic vs. non-academic) did not influence SLNB recommendations.DiscussionDespite a low response rate (8.3%), findings suggest that SLNB is widely performed by specialists across different practice settings, particularly for select tumor types. However, with 20% not performing SLNB and 37% uncertain about its reliability, these results highlight the need for standardized guidelines to define clear indications and improve consistency in clinical decision-making.